In vitro susceptibility studies of Cryptococcus neoformans isolated from patients with no clinical response to amphotericin B therapy - Rodero, Laura (2000)
Fil: Rodero, Laura. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Micología; Argentina.